A Novel Dual-Band Left-Handed Metamaterial Design Method - Si Li; Wenhua Yu; Atef Z. Elsherbeni; Wenxing Li; Yunlong Mao (International Journal of Antennas and Propagation)
A novel dual-band left-handed metamaterial (LHM) design method is proposed in this paper. Unlike other methods, where the designers focused their attentions on designing single LHM unit with multiple electric/magnetic resonances or combining multiple different LHM units together, the proposed method in this paper introduces an additional magnetic resonance to extract negative permeability, taking advantage of the areas between neighboring units. In this paper, we first designed a single-band single negative metamaterial (μ<0) and then connected neighboring units with metallic wires. This connection introduces a magnetic resonance that extracts another frequency band with negative permeability. With the help of arrayed metallic wires printed on the other side of the substrate, we successfully get a dual-band LHM. The proposed structures are analyzed with equivalent circuits and verified with simulations.